Gunung Api purba Watuadeg: Sumber erupsi dan posisi stratigrafi - Bronto, Sutikno; MulyaningSih, Sri; Hartono, G.; Astuti, B. (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no3.20081Pillow lava flows of pyroxene basalt containing 50 wt.% SiO are exposed at Opak River, west of Watuadeg Village, Sleman - Yogyakarta. The length of flow structures is between 2 â€“ 10 m, with diameter of 0.5 â€“ 1.0 m and it has a glassy skin at the surface body. Flow directions vary from N70E in the northern side, through N 120E in the middle to N 150E in the southern side. About 150 m away from the river to the west, there is a small hill about 15 m high, that has a similar composition with the pillow lavas. Both lava flows and the small hill are composed of pyroxene basalt, dark grey in color, hypocrystalline vitrophyre to porphyritic texture, with fine-grained phenocrysts of pyroxene (10 %) and plagioclase (25 %) set in glassy groundmass. These data indicate that the small hill was the eruption source of the basaltic pillow lavas. The lavas are overlain by pumice-rich volcaniclastic rocks, composed of tuff, lapillistones and pumice breccias, that are known as the Semilir Formation. Near the contact with lavas, the volcaniclastic rocks contain some fragments of pyroxene basalt, similar composition with the pillow lavas. This fact, together with analyses of petrology, volcanology, and radiometric dating show that the basaltic pillow lavas are unconformably overlain by the Semilir Formation. Â